A taRNA vaccine candidate induces a specific immune response that protects mice against Chikungunya virus infections - Christin Schmidt; Erik Haefner; Julia Gerbeth; Tim Beissert; Ugur Sahin; Mario Perkovic; Barbara S. Schnierle (Elsevier, 2022)
The arthritogenic alphavirus, chikungunya virus (CHIKV), is now present in almost 100 countries worldwide. Further spread is very likely, which raises public health concerns. CHIKV infections cause fever and arthralgia, which can be debilitating and last for years. Here, we describe a CHIKV vaccine candidate based on trans-amplifying RNA (taRNA). The vaccine candidate consists of two RNAs: a non-replicating mRNA encoding for the CHIKV nonstructural proteins, forming the replicase complex and a trans-replicon (TR) RNA encoding the CHIKV envelope proteins. The TR-RNA can be amplified by the replicase in trans, and small RNA amounts can induce a potent immune response. The TR-RNA was efficiently amplified by the CHIKV replicase in vitro, leading to high protein expression, comparable to that generated by a CHIKV infection. In addition, the taRNA system did not recombine to replication-competent CHIKV. Using a prime-boost schedule, the vaccine candidate induced potent CHIKV-specific humoral and cellular immune responses in vivo in a mouse model. Notably, mice were protected against a high-dose CHIKV challenge infection with two vaccine doses of only 1.5 μg RNA. Therefore, taRNAs are a promising safe and efficient vaccination strategy against CHIKV infections.